Seasonal body mass changes and feed intake in spectacled bears (Tremarctos ornatus) at Zurich Zoo - Gerstner, Kerstin; Liesegang, Annette; Hatt, Jean-Michel; Clauss, Marcus; Galeffi, Cordula (Journal of Zoo and Aquarium Research, 2016)
Many animals display seasonal patterns of behaviour and metabolism that can be also be observed in captivity. During an obesity-control program in Andean bears (Tremarctos ornatus) at Zoo Zurich, a seasonal fluctuation of body mass war observed once ideal body mass had been reached. The focus of this study was the question if metabolism of a male and three female animals was affected by seasonality according to their seasonal breeding behaviour, using data on pelleted food intake (from computer controlled feeders) and body mass (from regular weighing). The pelleted diet in the feeder boxes was provided additionally to a daily ration containing vegetables, fruits, pellets for environmental enrichment, and fish. This daily ration was adjusted, within prescribed limits, by the animal keepers depending on the previous day's consumption. Formulas developed for dogs were used to estimate the metabolizable energy (ME) content of the diet and maintenance requirement of the bears depending on their individual body mass. Energy requirements for minimum walked distances between the feeders was calculated as well as energy requirement for fat accretion or energy gained from body fat by body mass loss. Body mass showed a seasonal fluctuation with maxima in spring and minima in autumn, in contrast to the pattern typically observed in animals from the temperate zone; in the male, the body mass maximum occurred later than in the females. Feed intake from feeder boxes peaked in autumn, at the beginning of body mass gain in the females. These patterns cannot be explained as seasonal adaptations to climatic changes in the zoo environment, but match the natural breeding season of Andean bears in their natural habitat, suggesting genetically fixed photoperiodic clues. The data indicate that body mass fluctuation in a range considered ideal for the species was mostly based on the additional food whose amount was adjusted - within limits - by the keepers on a daily basis. Such adjustment, without incurring the risk of obesity in bears that are known as voracious eaters, is a good example of the skill required in animal husbandry.